Glucose-regulated protein 78 (Grp78/BiP) is secreted by human oviduct epithelial cells and the recombinant protein modulates sperm-zona pellucida binding - Marin Briggiler, Clara Isabel (2010)
To determine the secretion of Grp78 by human oviduct epithelial cells, its association to spermatozoa, and its involvement in gamete interaction. Prospective study. Basic research laboratory. Semen samples obtained from normozoospermic volunteers. Tubal tissue provided by patients undergoing hysterectomies. Oocytes collected from women undergoing IVF-ET. Analysis of Grp78 expression and secretion by oviductal tissue. Gamete incubation with recombinant Grp78 (rec-Grp78).